STRENGTHS AND WEAKNESSES OF E-WALLET SYSTEM IN AGRICULTURAL INPUT DISTRIBUTION AMONG FARMERS IN OSUN STATE, NIGERIA: IMPLICATIONS FOR SUSTAINABLE AGRICULTURAL DEVELOPMENT - Michael FAMAKINWA; Dorcas Lola ALABI; Lateef Ayodeji OLA; Rukayat Abiodun ADEYEMO (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study was designed to assess the strengths and weaknesses of e-wallet innovation system of agricultural input distribution among farmers in Osun State, Nigeria. A multistage stage sampling procedure was used to select the respondents. Data were gathered through structured interview schedule from 324 farmers randomly selected from four Local Government Areas of the state. Data collected were analyzed using appropriate descriptive and inferential statistical tools. The results showed that the respondents had a mean age of 44.1 years with majority (74.1% and 94.4%) were male and married respectively. The mean household size of the respondents was 9 persons. Removal of corruption on fertilizer (mean=2.53), access to fertilizers at subsidized price (mean=2.35), quickened access to improved seeds (mean=2.27) and elimination of exploitative activities of middlemen in fertilizer supply (mean=2.21) were the major strengths of the scheme. While low quantity of fertilizers allocated to farmers (mean=3.17), late supply of inputs (mean=3.05), poor mobile network for e-wallet (mean=3.02) and low level of awareness of e-wallet by farmers (mean=3.01) were the prominent weaknesses of e-wallet. It is therefore recommended that successive government should continue and improve on the approach by addressing the identified weaknesses since the system has great potentials for sustainable agricultural development in the nation.